Maternal Metabolic Health, Lifestyle, and Environment – Understanding How Epigenetics Drives Future Offspring Health - Amrom, Dalia; Schwartz, Stanley S. (Current Diabetes Reviews, 2023)
The incidence of metabolic disorders, such as obesity and type two diabetes (T2DM), continues to increase worldwide, and their onset is often attributed to adherence to a western diet and a sedentary lifestyle. However, large variability exists in one's likelihood of developing metabolic dysregulation, illustrating that our understanding of heritability patterns remains poorly understood. Diabetes and obesity are multifactorial diseases, and their onset is influenced by both genetic and environmental factors. Genome-wide association studies report a number of alterations in the coding sequence associated with the onset of T2DM and obesity. However, these genes explain only a fraction of the cases, leaving the majority unaccounted for. The missing heritability question implies that other factors are responsible for the onset and development of the disease. Given that the developing fetus is susceptible to the maternal environment, a growing body of evidence demonstrates that maternal metabolic characteristics as well as disruptions to the prenatal environment may induce long-term genetic, phenotypic, and physiologic adaptations in the developing fetus, which could have a permanent effect on its future health. This phenomenon is known as developmental programming and is mediated through epigenetic modifications, which include modulation of gene expressions that do not alter the original deoxyribonucleic (DNA) sequence. Epigenetic modifications are capable of changing gene expression in metabolism-related genes and are accomplished through DNA methylation, histone acetylation, and ribonucleic acid (RNA) mechanisms. In this review, we discuss maternal metabolic factors, such as obesity, dyslipidemia, and gestational diabetes (GDM) that lead to epigenetic changes in the offspring and predispose future generations to metabolic abnormalities. We will also describe the association between maternal lifestyle factors and exposure to toxins with epigenetic modulations in the offspring. Lastly, we will provide a brief review of the possibility of using epigenetics as potential interventions and therapeutic modalities to help in early diagnosis and prevention of metabolic disorders.
Keywords: obesity